Utilização do Google Maps para o ensino de coordenadas cartesianas mediada pelo geoplano - SOUZA, Mara Nayara Monteiro de (2024)
The objective is to explore how combining tools can improve understanding of geometric concepts and positively influence student performance. This study was carried out in a 2nd year high school class at a public school in the city of Salinópolis – PA. At the beginning, students are introduced to the basic concepts of Cartesian coordinates. Then, Google Maps is incorporated as an interactive tool, allowing students to choose real geographic points as references. The geoplane functioned as a tangible element, providing a physical connection with the abstract concepts of coordinates. We suggest that students position elastic bands on the geoplane to represent points on the Cartesian plane, creating a bridge between digital representation on the map and practical manipulation on the geoplane. During the activities, students were challenged to trace routes between different points on the map, using the Cartesian coordinates learned. As a result of this study, we can conclude that: it promoted not only the understanding of mathematical concepts, but also the development of spatial analysis and problem-solving skills. The proposal provided an opportunity not only to consolidate the understanding of Cartesian coordinates, but also stimulated critical thinking and the practical application of this knowledge in real-world situations, using Google Maps technology as an enriching educational resource.